Do Audit Fees and Characteristics of CEO Decrease Audit Delay in Mandatory IFRS Adoption? - Rizal Mawardi; Laela Lanjarsih (Bina Nusantara University, 2020)
The research examined characteristics of CEO and audit fees on audit delay related to changes in mandatoryIFRS adoption. In the setting, gender and audit fees were the level of risk tolerance, overconfidence, diligence,and monitoring intensity. As a result, these individual differences were likely to be reflected in audit delay infinancial reporting decisions. Using firm data levels between 2008 and 2016 with multivariate regression, theresearch provided empirical evidence supporting the hypothesis that the characteristics of CEO and audit feeswere the determinants of audit delay. There are several findings. First, the financial expertise of the CEO has moresignificant percentages in mandatory IFRS adoption than voluntary IFRS adoption. It is associated with a shorterdelay. Second, having a female CEO and appointing a female and minority CEO will increase the likelihood thatfirms will issue financial reports more timely. Third, higher audit fees in mandatory than voluntary IFRS adoptioncan decrease audit delay.